Tatbiq Wasail al-Kalimat al-Mutaqatha‘ah ‘Abra al-Intirnit ‘an Covid-19 li Irtifa’i Maharah al-Kitabah Laday at-Talabah - Ro’isatul Mamlu’ah; Nailul Izzah; Akla Akla; Muhammad Syaifullah; Faedurrohman Faedurrohman; Endang Munawar (Postgraduate of IAIN Metro Lampung Indonesia, 2021)
The lack of method and means in the educational process of the Arabic language. It made the students difficult to understand the material and feel bored and they think that the Arabic language is a difficult study and makes them bored especially in the skill of writing. With some of these problems, the researchers are applying online crossword puzzles to raise the writing skill of the tenth class students in the First Islamic State Secondary School Lampung Oriental, with the expectations that they can be fixed and the writing skill of the students will be raised. The method used in this research is the qualitative descriptive method. The result of this research is that the students can write the letters of the Arabic language well. They are able to form letters when the letters are at the beginning, middle or end of a word.